Mental health and governmental response policy evaluation on COVID-19 based on vaccination status in Republic of Korea - Dong-Kyu Kim; Inyup Lee; Chulhwan Choi; Sung-Un Park (BMC, 2023)
Abstract Background The coronavirus disease (COVID-19) pandemic has continued since the outbreak in December 2019. People experience depression and anxiety due to government policies and restrictions on physical activity due to the COVID-19 pandemic. This study aimed to compare and analyze people's experiences of COVID-19 blues, sports policy awareness, and participation intention according to their vaccination status. Methods This quantitative study used an online survey to collect demographic information, vaccination status, and variables. Data validity and reliability were verified through confirmatory factor analysis, and Cronbach's alpha coefficients were calculated using SPSS/AMOS 23.0. Finally, this comparative study was conducted using multivariate analysis of variance to investigate the differences in the dependent variables between the groups. Results The vaccinated group had higher scores for all factors related to COVID-19 blues (F = 19.147; p < .05; partial η 2  = .046) and government policy (market responsiveness: F = 5.669, p < .05, partial η 2  = .014; policy performance: F = 6.997, p < .05, partial η 2  = .017; policy satisfaction: F = 7.647, p < .05, partial η 2  = .019), apart from the intention to participate in sports (F = .014, p > .05, partial η 2  = .000); these results demonstrate that people with COVID-19 blues and relatively high confidence in government quarantine policies were more likely to be vaccinated. In addition, all participants gave sports-participation intention the highest rating, regardless of their vaccination status; this reflects the current situation, in which individual activities are limited. Conclusions This study analyzed the mental health of vaccinated and unvaccinated groups in Korean adult men, their perceptions of government policies, and their willingness to engage in physical activity. The findings are meaningful and highlight useful directions for future research. This study provides evidence which can help alleviate the mental damage caused by government quarantine policies and enable a better understanding of the COVID-19 pandemic. The results of this study provide important data for understanding the COVID-19 pandemic.